2014
DOI: 10.1073/pnas.1413445112
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal deferoxamine prevents pressure-induced diabetic ulcers

Abstract: There is a high mortality in patients with diabetes and severe pressure ulcers. For example, chronic pressure sores of the heels often lead to limb loss in diabetic patients. A major factor underlying this is reduced neovascularization caused by impaired activity of the transcription factor hypoxia inducible factor-1 alpha (HIF-1α). In diabetes, HIF-1α function is compromised by a high glucose-induced and reactive oxygen species-mediated modification of its coactivator p300, leading to impaired HIF-1α transact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
176
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(185 citation statements)
references
References 72 publications
9
176
0
Order By: Relevance
“…However, our findings also suggest that the abnormalities of the response of fibroblasts to hypoxia could be a contributing factor. Previous studies identified activation of hypoxia-inducible factor 1α and its inhibition by p300 as an important pathway that is abnormal in fibroblasts from diabetic patients, the normalization of which could improve wound healing (54,55). Thus, it is likely that abnormalities in wound healing, especially in fibroblasts, are caused by several important pathways that may be related to such phenomena as hyperglycemia, insulin resistance, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings also suggest that the abnormalities of the response of fibroblasts to hypoxia could be a contributing factor. Previous studies identified activation of hypoxia-inducible factor 1α and its inhibition by p300 as an important pathway that is abnormal in fibroblasts from diabetic patients, the normalization of which could improve wound healing (54,55). Thus, it is likely that abnormalities in wound healing, especially in fibroblasts, are caused by several important pathways that may be related to such phenomena as hyperglycemia, insulin resistance, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been shown to induce the production of cytokines and stimulate the proliferation and migration of fibroblasts and keratinocytes and local hypoxia in wounds could accelerate wound closure mediated by the HIF-1 (Li et al, 2007;Shen et al, 2009). Deferoxamine, an iron chelator has been used for the induction of HIF-1α accumulation even under normoxia (Martinez-Romero et al, 2008;Wu et al, 2010;Duscher et al, 2015). Notwithstanding the HIF-1α inducing property of deferoxamine and its indirect effect on several vital cellular processes, there is no available report on the effect of deferoxamine on diabetic wound healing after topical application.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is a master transcription factor, which not only activates VEGF expression, but a number of other genes also, that are important to wound healing (Rey and Semenza, 2010). Additionally, HIF-1α regulates many target genes involved in angiogenesis and has been reported to be reduced in the diabetic environment that may contribute to impaired wound healing (Botusan et al, 2008, Xing et al, 2011Duscher et al, 2015). In this study, topical application of deferoxamine significantly increased HIF-1α mRNA and protein levels from day 3 onwards and accelerated wound healing by stimulating vascularization through up-regulation of VEGF and SDF-1α in an HIF-1α-dependent manner.…”
Section: Deferoxamine Stimulated Vascularization Through Up-regulatiomentioning
confidence: 99%
“…This generates a hypoxic microenvironment 34,35 . Degranulation of platelets and mast cells in the plug along with hypoxia-inducible factors release more than three hundred active substances including cytokines, chemokines, inflammatory mediators and bioactive molecules within minutes to 5 days after injury, drawing in neutrophils and monocytes, and activating macrophages within the wound 36,37 .…”
Section: Macrophages In Wound Healingmentioning
confidence: 99%
“…These macrophages release tumor necrosis factor (TNF-α) and hydroxyl radicals, bringing about senescence in fibroblasts 92 . Iron chelators such as deferoxamine are FDA-approved for systemic use in patients with hemoglobinapathies 35 . Their indication can be extended to chronic wounds with iron-overload to reduce local macrophage-induced inflammation and promote the healing response.…”
Section: Macrophages In Chronic Woundsmentioning
confidence: 99%